Palliative care needs of patients living with end-stage kidney disease not treated with renal replacement therapy: An exploratory qualitative study from Blantyre, Malawi - Maya J. Bates; Alex Chitani; Gavin Dreyer (AOSIS, 2017)
Background: The burden of end-stage kidney disease (ESKD) in sub-Saharan Africa is increasing rapidly but the palliative care needs of patients living with ESKD are not well described. Resource limitations at both health system and patient level act as major barriers to patients receiving renal replacement therapy (RRT) in the form of dialysis. We undertook an exploratory qualitative study to describe the palliative care needs of patients with ESKD who were not receiving RRT, at a government teaching hospital in Blantyre, Malawi. Methods: A qualitative, explorative and descriptive design was used. Study participants were adults aged > 18 years with an estimated glomerular filtration rate < 15 ml/min on two separate occasions, three months apart, who either chose not to have or were not deemed suitable for RRT. Data were collected by means of semi-structured interviews. Results: In October and November 2013, interviews were conducted with 10 adults (7 women with median age of 60.5 years). All were hypertensive and four were on treatment for HIV. Four themes emerged from the data: changes in functional status because of physical symptoms, financial challenges impacting hospital care, loss of role within the family and the importance of spiritual and cultural beliefs. Conclusion: This study reports on four thematic areas which warrant further quantitative and qualitative studies both in Malawi and other low-resource settings, where a growing number of patients with ESKD unable to access RRT will require palliative care in the coming years.